2022
DOI: 10.1155/2022/6814901
|View full text |Cite
|
Sign up to set email alerts
|

Study of Antibacterial Activity of Root Bark, Leaves, and Pericarp Extracts of Diploknema butyracea and Evaluation of Prospective Antioxidant Activity

Abstract: This study was aimed to determine the antibacterial activity of root bark, leaves, and pericarp extract of Diploknema butyracea and to evaluate the prospective antioxidant activity, total flavonoid, polyphenol, and carbohydrate content. The plant parts were collected and extracted by cold maceration, using hexane, ethyl acetate, methanol, and distilled water. Phytochemical screening of different samples of D. butyracea in different solvents revealed the presence of varied extent of alkaloid, saponin, terpenoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 31 publications
(40 reference statements)
2
9
0
Order By: Relevance
“…On the other hand, the bark extract exhibited the highest amount of TPC and TFC amongst other tested extracts of D. malabarica . The results showed that methanol bark extract amongst other extracts could be more effective and fight against free radicals because antioxidant capability is determined by phytochemical contents as it was found in partial agreement of earlier report [ 47 , 48 ] which demonstrated that antioxidant potency of methanol bark extract of D. malabarica might be due to the greatest presence of well-known natural antioxidants such as polyphenol, tannins, and flavonoids. Of all phytochemicals, polyphenols are greatly identified as an antioxidant anti-inflammatory, antiviral, and antimicrobial agents [ 49 ].…”
Section: Resultssupporting
confidence: 88%
“…On the other hand, the bark extract exhibited the highest amount of TPC and TFC amongst other tested extracts of D. malabarica . The results showed that methanol bark extract amongst other extracts could be more effective and fight against free radicals because antioxidant capability is determined by phytochemical contents as it was found in partial agreement of earlier report [ 47 , 48 ] which demonstrated that antioxidant potency of methanol bark extract of D. malabarica might be due to the greatest presence of well-known natural antioxidants such as polyphenol, tannins, and flavonoids. Of all phytochemicals, polyphenols are greatly identified as an antioxidant anti-inflammatory, antiviral, and antimicrobial agents [ 49 ].…”
Section: Resultssupporting
confidence: 88%
“…However, antimicrobial activity was determined to below for B. sphaericus and P. vulgaris (Graph II). Similar findings were reported in stem, bark extracts of Lophira lanceolata [17] , stem extract of Diploknema butyracea [18] and stem extracts of Solanum khasianum [19] . The different concentrations of root butanolic extract (20 µg/ml, 40 µg/ml, 60 µg/ml, 80 µg/ml) were tested for its antibacterial property with reference to the control (10 µg/ml).…”
Section: Antibacterial Activitysupporting
confidence: 88%
“…DPPH Radical Scavenging Assay. Te free radical scavenging capacity of the EOs was estimated following the DPPH free radical method [19] with slight modifcations. Te DPPH solution was prepared by dissolving 2.4 mg of DPPH in 100 mL of absolute ethanol.…”
Section: Determination Of Antioxidant Activitymentioning
confidence: 99%